RELEVANCE OF FREE CASH FLOW AS A MEASURE OF GENERATING VALUE FOR OWNERS - Bešlić, Ivana; Bešlić, Dragana; Rupić, Bojan (International Journal of Economic Practice and Policy, 2014)
In the new economy or knowledge economy the main goal of any company should be directed towards the achievement of the business in the interest of the owners, or generating the value for owners. In dynamic business environment, an effective performance measurement system is key determinant of successful implementation of corporate strategy, growth and survival of the company. Modern performance measures should provide an accurate assessment of the intrinsic value of the company, as well as the value for the owners (shareholders). The essence is maximizing the immanent or guaranteed value of the company. The immanent value is the value of a company based on internal evaluation (assessment discounted cash flows or expected cash flow in the future) by the management team. Corporate managers in Serbia are facing the challenge of increasingly efficient capital markets and the competition in the future, which requires the implementation of a value oriented corporate governance, therefore this paper presents FCF (Free Cash Flow) methodology of valuation. Free cash flow (FCF) is the amount of cash available for owners of the company after the necessary investments in fixed assets and working capital to maintain the current scope of activities and support to planning.
Keywords: development; effectiveness; evaluation; value; performance; period; FCF